A review of immunization legislation for children in English- and Dutch-speaking Caribbean countries - Tracy Evans-Gilbert; Karen N. Lewis-Bell; Beryl Irons; Philippe Duclos; Gabriel Gonzalez-Escobar; Elizabeth Ferdinand; J. Peter Figueroa; on behalf of the Caribbean Immunization Technical Advisory Group (Pan American Health Organization, 2023)
Objective. To assess the legislative frameworks concerning childhood vaccination in the English- and Dutch-speaking Caribbean and propose a model legislative framework for Caribbean countries. Methods. This study included a survey of 22 countries and territories in the Caribbean regarding legal vaccination mandates for school entry, budget allocations, sanctions, or exemptions. A legal consultant conducted a comprehensive search and analysis of legislation regarding vaccination among 13 Caribbean countries/territories. A comparative analysis of the legislation under five themes-legislative structure, mandatory vaccination, national immunization schedule, sanctions, and exemptions-formed the basis for the proposed model legislation. Results. Among the 22 Caribbean countries/territories, 17 (77%) had legislation mandating vaccination, 16 (94%) mandated vaccination for school entry, 8 (47%) had a dedicated budget for immunization programs, and 13 (76%) had no legislated national schedules. The source of legislation includes six (35%) using the Education Act, eight (47%) the Public Health Act, and five (29%) a free-standing Vaccination Act. Three countries/territories-Jamaica, Montserrat, and Saint Lucia-had immunization regulations. In 12 (71%) of the 17 countries with legislation, sanctions were included, and 10 (59%) permitted exemptions for medical or religious/philosophical beliefs. Conclusions. Several countries in the Caribbean have made failure to vaccinate a child an offense. By summarizing the existing legislative frameworks and approaches to immunization in the Caribbean, the analysis guides policymakers in making effective changes to immunization legislation in their own countries.